Travel-Related Risk Behaviors and Antibiotic Use Among Older Travelers. (28th July 2021) - Costello, Varea H; Tribble, David; Eickhoff, Christa; Tilley, D Hamilton; Utz, Gregory; Telu, Kalyani; Ganesan, Anuradha; Fraser, Jamie; Lalani, Tahaniyat
Abstract: Background: Antibiotic stewardship in the pretravel care of older adults is important to effectively treat infections while minimizing harm from side effects and unnecessary antibiotic use. The objective of this study was to compare the characteristics, risk behaviors, infectious diseases, and antibiotic use between older (≥60 years) and younger (18–59 years) travelers. Methods: TravMil is a prospective, observational cohort of United States (US) Department of Defense beneficiaries traveling outside the continental US for ≤6.5 months. For this analysis, we included adults enrolled pretravel between January 2010 and August 2018 and excluded active duty personnel on deployment. Pre and post-travel surveys captured trip characteristics, exposures, illnesses, and antibiotic use. Results: A total of 1742 travelers were analyzed: 747 (42.9%) were aged ≥60 years and 995 (57.1%) were aged 18–59 years. Older travelers were less likely to engage in high-risk dietary behaviors and experience travelers' diarrhea than younger travelers (18.2% vs 22.9%; P  < .05). Influenza-like illness (12.5%) and febrile illness (3.4%) occurred less frequently in the older cohort. Antibiotic use for self-treatment was common in both age groups (25.7% vs 26.7%) and often inappropriate, for example, for treatment of occasional loose stool or mild travelers' diarrhea (67.0% [67/100] in older adults vs 57.6% [83/144] in younger adults; P  < .05), and influenza-like illness (63.4% [64/101] vs 58.6% [68/116], respectively; P  < .05). Conclusions: Older travelers were less likely to engage in high-risk behaviors and experience travelers' diarrhea, and both age groups experienced mild, self-limited infections. Inappropriate use of antibiotics was common, suggesting that antimicrobial stewardship should be emphasized at pretravel counseling with international travelers. Abstract : Older travelers (≥60 years) are less likely to engage in high-risk dietary behaviors and experience travelers' diarrhea than younger travelers (18–59 years). Antibiotics are often used inappropriately for mild or self-limited diarrhea and influenza-like illnesses during travel.